Independent Labels? The Power behind Environmental Information about Products and Companies. (March 2015) - Bullock, Graham
Power is a ubiquitous term in political science, and yet the discipline lacks a metric of power that can be applied to both formal and informal political contexts. Building on past work on power and power resources, this paper develops a method to estimate the power of different actors over an organization. It uses this method to analyze the power of the public, private, and civil sectors within an original dataset of 245 cases of product and corporate environmental evaluations, such as ENERGY STAR, LEED Certification, and Newsweek's Greenest Company Rankings. These initiatives have received limited attention from the political science literature, but they have become an increasingly prominent political phenomenon. The paper finds that the private and civil sectors likely have more power over these information-based governance initiatives than the public sector. It also reveals their lack of transparency and hybrid accountability relationships, which complicate their legitimacy and effectiveness.